Study protocol for randomised clinical trial comparing the effectiveness of side-lying sleep positioning to back-lying at reducing oxygen desaturation resulting from obstructive sleep apnoea in infants with cleft palate (SLUMBRS2). Issue 4 (7th April 2021) - Metryka, Aleksandra; Cunniffe, Claire; Evans, Hazel J; Gavlak, Johanna G; Hudson, Nichola; Kirby, Nigel; Lakhanpaul, Monica; Lin, Yin-Ling; Murray, Clare; Rajai, Azita; Robson, Helen; Schilder, Anne; et al.
Abstract : Introduction: The craniofacial abnormalities found in infants with cleft palate (CP) decrease their airway patency and increase their risk of obstructive sleep apnoea (OSA). We hypothesise that optimising sleep position in infants with CP may improve airway patency and offer a 'low-cost, high-impact' intervention to prevent the negative impacts of OSA. Because cleft centres give inconsistent advice about sleep position: some recommend back-lying and others side-lying, we will compare these in a randomised controlled trial. Methods and analysis: The aim is to determine the clinical effectiveness of side-lying as compared with back-lying sleep positioning in terms of reducing oxygen desaturation resulting from OSA in 244 infants aged 3–5 weeks of age, diagnosed with an isolated CP in/by UK cleft centres. Primary outcome is the 4% Oxygen Desaturation Index measured using pulse oximetry during sleep. Research plan: 1. Multicentre randomised controlled trial of side-lying compared with back-lying sleep positioning in reducing oxygen desaturation resulting from OSA in infants with CP at one month of age. 2. Internal pilot questionnaire-based study to support parents and clinicians regarding study participation, seeking to identify and address any barriers to recruitment. Monitoring data from the internal pilot will be used in the final analysis. 3. Co-development of new UK recommendations with Cleft Lip and Palate Association (CLAPA) regarding sleep position for infants with CP. Ethics and dissemination: The study protocol has received the favourable opinion of the West Midlands-South Birmingham Research Ethics Committee. Study results will be published on affiliated webpages and in peer-reviewed publications and conference contributions. Trial registration number: NCT04478201 .